Serological and Molecular Investigation of Infectious Laryngotracheitis Virus in Chickens from Robe Town, Southeastern Ethiopia - Samuel Abebe; Gianmarco Ferrara; Belayneh Getachew; Eyob Hirpa; Nebyou Moje (Animals, 2024)
Infectious laryngotracheitis virus (ILTV) is responsible for avian infectious laryngotracheitis (ILT), a highly contagious acute respiratory disease affecting chickens. However, there is limited information on ILTV and its distribution in Ethiopia, particularly in the southeastern region. The aim of this study was to establish the serological prevalence and molecular evidence in commercial and backyard chickens from Robe town, Southeastern Ethiopia. A cross-sectional study was conducted between December 2021 and June 2022, collecting 240 serum samples from randomly selected chickens belonging to eight kebeles (farms) using systematic random sampling. ILTV-specific antibodies were detected using a commercial indirect enzyme-linked immunosorbent assay (ELISA). From 240 serum samples, 26.7% were positive for ILTV antibodies. Logistic regression analysis identified the type of poultry farm (backyard) and the introduction of chickens from other farms as potential risk factors associated with ILTV exposure. Tracheal tissue and oropharyngeal and tracheal swabs were collected from suspected chickens for isolation and molecular detection. A total of six samples were successfully isolated in embryonated eggs (40%), with four of them verified with a specific PCR. These findings documented the presence of ILTV in the study area, which needs further insight to fully understand the actual spread of ILTV and quantify the damage caused to the poultry sector.